COGNITION IN FORMER RUGBY UNION PLAYERS AND IMPACT OF CONCUSSION HISTORY. Issue 4 (1st February 2017) - Hume, Patria; Theadom, Alice; Lewis, Gwyn N; Quarrie, Kenneth L; Brown, Scott R; Hill, Rosamund; Marshall, Stephen W.
Abstract : Background: Information is needed on the effects on health after retirement from participating in sport and any effects of sustaining concussions. Objective: To investigate differences in cognitive function between former rugby and non-contact sport players, and any association between concussion history and cognitive function. Design: Cross sectional descriptive study. Comparisons across player groups, concussion groups (one or more self-reported concussions versus no concussions) and between these groups with CNS-vital signs age-matched norms (US norms). Setting: On-line data collection. Participants: 366 former players (mean ±SD age 43.3±8.2 years); 103 elite rugby, 193 community rugby, 65 non-contact sport. Assessment of Risk Factors: Concussion history was obtained from an on-line self-report questionnaire. Cognitive functioning was assessed using the online CNS-vital signs neuropsychological test battery. Main Outcome Measurements: CNS-vital signs test scores and concussion counts. Results: The former elite rugby union player group had deficits in cognitive functioning relative to the non-contact sport player group as indicated by complex attention, cognitive flexibility, processing speed and executive functioning scores using the CNS-vital signs test. The former community rugby group performed worse than non-contact sports players on cognitive flexibility and executive functioning tests. Community and elite former rugby union players reported a substantially higher number of concussions than non-contact sport players. The player group who had experienced one or more concussions, had deficits in cognitive flexibility, complex attention, and executive function relative to the player group with no history of concussion. Conclusions: Past participation in rugby, or history of concussion, were associated with small to moderate neurocognitive deficits, as indicated by worse CNS-vital signs scores. A greater proportion of former rugby players than expected showed deficits in composite memory, verbal memory, and reaction time, in addition to processing speed and complex attention for elite rugby, and psychomotor speed and motor speed for community rugby.